The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s12913-020-05096-7
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with institutional delivery in Ethiopia: a cross sectional study

Abstract: Background: In spite of the promotion of institutional delivery in Ethiopia, home delivery is still common primarily in hard-to-reach areas. Institutional delivery supported to achieve the goal of reducing maternal and neonatal mortality in Ethiopia. The objective of this study is to assess the determinants of institutional delivery in Ethiopia. Methods: Cross sectional survey was conducted in 11 administrative regions of Ethiopia. The Ethiopian demographic and health survey data collection took place from Jan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 9 publications
10
20
1
Order By: Relevance
“…Our study also showed that wealth status is signi cant predicator of institutional delivery both with and without controlling other variables. The result are similar with the study conducted in Bangladesh 21 Gambila 22 , Southwest Ethiopia 23 ,and Mozambique 24 . The nding is also consistent with other studies Pakistan 25 , Eastern Nepal 26 and other different low income countries [27][28][29][30] .Despite of the Nepal's national agship programs (Aama) since 2005 which promoting safe motherhood through initiatives such as providing free delivery care and transportation incentive schemes to women delivering in a health facility, it is discouraging that poor women are less likely to deliver their recent child in the health facilities.…”
Section: Multivariate Analysissupporting
confidence: 89%
“…Our study also showed that wealth status is signi cant predicator of institutional delivery both with and without controlling other variables. The result are similar with the study conducted in Bangladesh 21 Gambila 22 , Southwest Ethiopia 23 ,and Mozambique 24 . The nding is also consistent with other studies Pakistan 25 , Eastern Nepal 26 and other different low income countries [27][28][29][30] .Despite of the Nepal's national agship programs (Aama) since 2005 which promoting safe motherhood through initiatives such as providing free delivery care and transportation incentive schemes to women delivering in a health facility, it is discouraging that poor women are less likely to deliver their recent child in the health facilities.…”
Section: Multivariate Analysissupporting
confidence: 89%
“…This finding was in line with 74%, 15 74.4%, 22 78.3%, 2 78.8% 16 studies conducted in Ethiopia and 78.1% in Gambia. 20 It was higher than 12.3%, 8 16.9% 29 24.8%, 5 26.2%, 19 31.0%, 9 32.8%, 30 47.3%, 18 63.1%, 31 64.62%, 14 64.8%, 21 71.2% 13 studies conducted in Ethiopia and 67.3% in Tanzania. 32 The variation observed could be due to socio-economic; educational and sociocultural profiles.…”
Section: Discussionmentioning
confidence: 89%
“…This finding was supported by several studies conducted previously. 1,2,[19][20][21]29,30,32 This is due to the better affordability of the cost incurred from the transportation and the service itself.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations